Chinese workers' history: passive minds docile bodies. Issue 3 (11th October 2019) - Leung, Elly; Caspersz, Donella
Abstract : Purpose: This paper aims to describe an exploratory study that has sought to understand how an institutionalised docility rather than resistance has been created in the minds of Chinese workers by the Chinese State. The study proposes that this docility has been crucial in enabling China to become a world leading economic powerhouse. Design/methodology/approach: The paper draws on Foucault's concept of governmentality and uses the genealogical method to examine the historical events that have shaped the mentalities of today's Chinese workers. Original interviews ( n  =   74) with everyday workers across industries and locations illustrate this. Findings: It was found that the utilisation of centuries-long Confucian hierarchical rules by successive regimes has created a cumulative effect that has maintained workers docility and their willingness to submit themselves to poor working conditions that – ultimately – benefit the Chinese State and business, though this is at their expense. This finding is in juxtaposition to current research that claim that their working conditions are fostering a rising consciousness and resistance among Chinese workers. Originality/value: This paper provides a novel explanation for why Chinese workers accept their poor working conditions and thus critiques current perspectives about Chinese worker resistance.